Model of Multi-Criteria Selection of Traditional Suppliers - Sysoiev, Volodymyr Viktorovych (European Research Center of Managerial Studies in Business Administration, 2017)
Efficient supply chain management is based on the strategic cooperation of many companies (suppliers and consumers), which involves long-term interaction with business partners. To ensure a reliable supply, most of the modern companies simultaneously interact with multiple suppliers of identical products, distributing the orders between them depending on many factors characterising suppliers, their products, and supply processes in previous periods. Under these conditions, the solution of the problem of multi-criteria selection of traditional suppliers is carried out by optimising purchase amounts of different product types in accordance with the needs of the consumer company based on many criteria. The main selection criteria are supply reliability and logistics costs of the purchase and product delivery. The generalised criterion for the assessment of supply reliability reflects the results of the interaction with suppliers in previous periods and includes assessment of completeness, package contents, timeliness of supply, and quality of supplied products. The logistics costs criterion shows the rejection of product prices offered by traditional suppliers and delivery costs from the minimum values of these indicators in the markets at the time of making procurement decisions. The paper contains the developed linear programming model, which allows optimising the procurement of different types of products from several traditional suppliers under the objective function, combining the evaluation criteria of supply reliability and logistics costs. The list of suppliers for each type of product is determined by the optimisation results. The method for selection of traditional suppliers is based on the proposed mathematical model and has a numerical example illustrating its application.
Keywords: traditional supplier; multi-criteria selection; supply reliability; logistics costs; linear programming model; procurement optimization